2016
DOI: 10.1159/000451012
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Transformation of Hepatocellular Adenoma

Abstract: The patient was a 20-year-old male in whom a hepatic hypervascular mass accompanied by intratumoral hemorrhage was detected on examination for epigastric pain. Based on the enlargement of the mass and diagnostic imaging, hepatocellular adenoma (HCA) was suspected and hepatectomy was performed. The lesion was diagnosed as malignant transformation of β-catenin-activated HCA. There are only few reports of cases with malignant transformation of HCA in Japan; it is necessary to accumulate cases to investigate it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Two of these patients had follow-up information (1 year and 9 years) with no evidence of recurrent disease. Twenty-six additional β-catenin mutated hepatocellular adenoma patients with malignant transformation previously reported in the literature were included in the analysis [12][13][14][15][16][17][18][19][20][21][22]. These patients were mostly male (65% male and 35% female) with an average age of 42 ± 14 years at the time of diagnosis (range: 20-66 years).…”
Section: Patients With Malignant Transformation Of β-Catenin Mutated ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Two of these patients had follow-up information (1 year and 9 years) with no evidence of recurrent disease. Twenty-six additional β-catenin mutated hepatocellular adenoma patients with malignant transformation previously reported in the literature were included in the analysis [12][13][14][15][16][17][18][19][20][21][22]. These patients were mostly male (65% male and 35% female) with an average age of 42 ± 14 years at the time of diagnosis (range: 20-66 years).…”
Section: Patients With Malignant Transformation Of β-Catenin Mutated ...mentioning
confidence: 99%
“…CharacteristicsLFABP-deficient hepatocellular adenomas β-catenin mutated hepatocellular adenomas a[12][13][14][15][16][17][18][19][20][21][22] P value HCC hepatocellular carcinoma, LFABP liver fatty acid binding protein, BCS Budd-Chiari syndrome, MODY maturity-onset diabetes of the young, DM diabetes mellitus, OCP oral contraceptive pills, GSD glycogen storage disease a β-catenin mutated hepatocellular adenoma cases included 4 cases from primary authors' institution and 26 cases from the literature[12][13][14][15][16][17][18][19][20][21][22] (see Supplementary Table1for details)…”
mentioning
confidence: 99%
“…Our results differ in some respects from those of the other two Japanese reports, 8,9 as shown in Table 2, which may reflect differences in the number of HCA cases examined, specimens being Association with HCA and HCC were found in three cases out of 38 HCA cases examined. In Japan, reports of malignant transformation of HCA are few, 13 such that the observations made in this investigation are important. Sasaki et al 8 reported one of their 13 cases (7.7%) to…”
Section: Discussionmentioning
confidence: 90%
“…Association with HCA and HCC were found in three cases out of 38 HCA cases examined. In Japan, reports of malignant transformation of HCA are few,13 such that the observations made in this investigation are important. Sasaki et al8 reported one of their 13 cases (7.7%) to show an association between HCA and HCC, while three of our 38 cases (7.9%) showed such an association.…”
mentioning
confidence: 90%
“…Kwok et al [4] report a case of malignant transformation of hepatocellular adenoma (HCA) in a 20-year-old male; this disease is very rare in Japan. Although the factors underlying HCA development are unclear, the diagnosis of β-catenin-activated HCA was correct in this case, in which HCC with similar immunopathological features and structural atypia might have developed from β-catenin-activated HCA.…”
mentioning
confidence: 99%